2020
DOI: 10.1140/epjc/s10052-020-8029-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the charge barrier height on Germanium (Ge) detectors with amorphous-Ge contacts for light dark matter searches

Abstract: Germanium (Ge) detectors with ability of measuring a single electron-hole (e-h) pair are needed in searching for light dark matter (LDM) down to the MeV scale. We investigate the feasibility of Ge detectors with amorphous-Ge (a-Ge) contacts to achieve the sensitivity of measuring a single e-h pair, which requires extremely low leakage current. Three Ge detectors with a-Ge contacts are used to study the charge barrier height for blocking electrons and holes. Using the measured bulk leakage current and the Döhle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Leakage currents measured at higher temperatures were higher than those at lower temper- atures. Such a temperature dependence is well documented in the literature [41][42][43][44][45][46][47]. The difference between the LAr and vacuum measurements at similar temperatures may have two possible explanations.…”
Section: Characterization In Vacuum Againsupporting
confidence: 54%
See 1 more Smart Citation
“…Leakage currents measured at higher temperatures were higher than those at lower temper- atures. Such a temperature dependence is well documented in the literature [41][42][43][44][45][46][47]. The difference between the LAr and vacuum measurements at similar temperatures may have two possible explanations.…”
Section: Characterization In Vacuum Againsupporting
confidence: 54%
“…A detailed study of the leakage currents of the USD detectors can be found in Ref. [47]. On average, the bulk leakage is around a few pA, the surface leakage is around a few tens of pA, at 78 K. In contrast, detectors made at LBNL using USD crystals typically have a combined leakage below 1 pA.…”
Section: Detector Characterization In Vacuummentioning
confidence: 99%
“…It is seen that the barrier heights of the prepared junctions range between 0.61 to 0.84 eV and are higher than the barrier height of germanium-based diodes, which have values in the range of 0.2–0.3 eV. 54,55 This gives the prepared samples a good chance to contribute to germanium based photodetection applications.…”
Section: Resultsmentioning
confidence: 93%
“…A detailed study of the leakage currents of the USD detectors can be found in Ref. [37]. On average, the bulk leakage is around a few pA, the surface leakage is around a few tens of pA, at 78 K. In contrast, detectors made at LBNL using USD crystals typically have a combined leakage below 1 pA.…”
Section: Detector Characterization In Vacuummentioning
confidence: 99%